Assessment of Health-Promoting Lifestyle among Dental Students in Zagreb, Croatia - Larisa Musić; Tonći Mašina; Ivan Puhar; Laura Plančak; Valentina Kostrić; Mihaela Kobale; Ana Badovinac (MDPI AG, 2021)
As future healthcare professionals, dental medicine students are expected to exhibit healthy lifestyle behaviors. This study aims to assess the health-promoting behaviors among undergraduate dental medicine students of all six academic study years at the University of Zagreb, and determine their predictors. Students were invited to complete a two-part survey, consisting of a self-reported sociodemographic questionnaire and the Health-Promoting Lifestyle Profile II (HPLP II). Three hundred and forty-nine students completed the survey; the response rate was 60.3%. The total mean HPLP II score was 2.64 ± 0.34. Students in the second academic study year scored the lowest (2.50 ± 0.33), and students in the sixth academic study year scored the highest (2.77 ± 0.32). Health responsibility was the overall lowest scored subcategory, while interpersonal relations was scored the highest. Female students reported lower spiritual growth and stress management than male students. Higher body mass index (BMI) was related to lower health responsibility. Smoking, place of residence and the age of participants did not seem to have an impact on health-promoting behaviors. Dental students at our faculty exhibit moderate health-promoting behaviors, even in the absence of a formal health-promoting course in the existing curriculum.